Influence of Non-canonical DNA Bases on the Genomic Diversity of Tevenvirinae - Nikulin, Nikita A.; Zimin, Andrei A. (Frontiers in Microbiology, 2021)
The Tevenvirinae viruses are some of the most common viruses on Earth. Representatives of this subfamily have long been used in the molecular biology studies as model organisms – since the emergence of the discipline. Tevenvirinae are promising agents for phage therapy in animals and humans, since their representatives have only lytic life cycle and many of their host bacteria are pathogens. As confirmed experimentally, some Tevenvirinae have non-canonical DNA bases. Non-canonical bases can play an essential role in the diversification of closely related viruses. The article performs a comparative and evolutionary analysis of Tevenvirinae genomes and components of Tevenvirinae genomes. A comparative analysis of these genomes and the genes associated with the synthesis of non-canonical bases allows us to conclude that non-canonical bases have a major influence on the divergence of Tevenvirinae viruses within the same habitats. Supposedly, Tevenvirinae developed a strategy for changing HGT frequency in individual populations, which was based on the accumulation of proteins for the synthesis of non-canonical bases and proteins that used those bases as substrates. Owing to this strategy, ancestors of Tevenvirinae with the highest frequency of HGT acquired genes that allowed them to exist in a certain niche, and ancestors with the lowest HGT frequency preserved the most adaptive of those genes. Given the origin and characteristics of genes associated with the synthesis of non-canonical bases in Tevenvirinae, one can assume that other phages may have similar strategies. The article demonstrates the dependence of genomic diversity of closely related Tevenvirinae on non-canonical bases.